Sensory Imagery in Individuals who Are Blind and Sighted: Examining Unimodal and Multimodal Forms. (July 2014) - Eardley, Alison F.; Pring, Linda
Introduction: Previous research has suggested that visual images are more easily generated, more vivid, and more memorable than other sensory modalities. This research examined whether or not imagery is experienced in similar ways by people with and without sight. Specifically, the imageability of visual, auditory, and tactile cue words was compared. The degree to which images were multimodal or unimodal was also examined. Methods: Twelve participants who were totally blind from early infancy and 12 sighted participants generated images in response to 53 sensory and nonsensory words, rating imageability and the sensory modality, and describing images. From these 53 items, 4 subgroups of words that stimulated images that were predominantly visual, tactile, auditory, and low-imagery were created. Results: T-tests comparing imageability ratings from blind and sighted participants found no differences for auditory and tactile words (both p > .1). Nevertheless, although participants without sight found auditory and tactile images equally imageable, sighted participants found images in response to tactile cue words harder to generate than visual cue words (mean difference: −0.51, p = .025). Participants with sight were also more likely to develop multisensory images than were participants without sight (both U ≥ 15.0, N1 = 12, N2 = 12, p ≤.008). Discussion: For both the blind and sighted groups, auditory and tactile images were rich and varied, and similar language was used. Sighted participants were more likely to generate multimodal images, and this was particularly the case for tactile words. Nevertheless, cue words that resulted in multisensory images were not necessarily rated as more imageable. The discussion considers whether or not multimodal imagery represents a method of compensating for impoverished unimodal imagery. Implications for practitioners: Imagery is important not only as a mnemonic in memory rehabilitation, but also in everyday uses for modes such as autobiographical memory. This research emphasizes the importance of not only auditory and tactile sensory imagery, but also spatial imagery for people without sight.